The Relationship Between Intuitive Eating, Eating Disorders, and Body Image Perceptions in Young Adult Women - Kocyigit, Emine; Uzunlar, Elif Adanur; Ozer, Sehriban Duyar; Zakkour, Hazal Kucukkaraca; Akbulut, Gamze (IOS Press, 2022)
BACKGROUND: The term intuitive eating is a new concept that has emerged in recent years. It is a way of eating that is based on responding to the body's natural signals of hunger and satiety. OBJECTIVE: The study was conducted to evaluate the relationship between intuitive eating and eating disorders and body image perception in young adult women. METHODS: The study was conducted with 400 women aged 19-35 years. The data were collected with the Figure Rating Scale, the Intuitive Eating Scale-2 (IES-2), and the Eating Attitude Test-26. RESULTS: The mean body mass index was significantly higher in individuals who misperceived their body image. While 51.4% of the participants with normal eating behavior had appropriate body image perception, 38.8% of the participants with abnormal eating behavior had appropriate body image perception. The IES-2 total score was significantly lower in women with abnormal eating behavior and overweight/obese women. CONCLUSIONS: Our findings showed that intuitive eating is negatively associated with abnormal eating behavior and obesity in young adult women and that women with low intuitive eating inclinations misperceived their body image.
Koçyigit, Emine/0000-0002-9459-9557; Kucukkaraca Zakkour, Hazal/0000-0002-3950-9280
Keywords: Eating Disorder; Body Image Perception; Intuitive Eating; Obesity; Body Mass Index